Answer: 8
Step-by-step explanation:
let x = the number
(x + 2)*10 = 8x + 36
10x + 20 = 8x + 36
2x = 16
x = 8
Mark as brainlist___________________________________
Answer:
6
Step-by-step explanation:
(8/3) / (-4/9)
when dividing fractions you use the acronym k.c.f (keep change flip)
keep the first fraction
change the operation (divide to multiply)
flip the other fraction
(8/-3) x (9/4)
after re-writing your expression, you want to solve
do this by multiplying both numerators by each other and same with the denominators
(-8x9) / (3x-4)
then you get a new fraction,
-72/-12
simplify,
-72/-12 = 6 (multiplying/dividing 2 negatives will always give you a positive)
-5x +2/9 +2x- 2/9 =7/9
collect like terms
-3x+0=7/9
cross-multiply
-27x=7
solve for x
x=-7/27
Answer:
6 + 8x
Step-by-step explanation: